A study on factors that contribute to the organizational commitment among employees of Trans Resources Corporation Sdn Bhd and Lembaga Zakat Selangor / Siti Norjannatul Nai’mah Mohd Halim and Wan Nurfarahin Wan Zahari - Mohd Halim, Siti Norjannatul Nai’mah; Wan Zahari, Wan Nurfarahin (2013)
A study was conducted to determine middle management employees of Trans Resources Corporation Sdn. Bhd and Lembaga Zakat Selangor perception on organizational commitment. The study analyzed whether or not there is a significant relationship between job satisfaction, job involvement, perceived organizational support and organizational commitment among the middle management employees. Data were collected by using questionnaires from 220 employees of two different organizations which are Trans Resources Corporation Sdn. Bhd. and Lembaga Zakat Selangor.